Endoplasmic reticulum stress and disturbed calcium homeostasis are involved in copper-induced alteration in hepatic lipid metabolism in yellow catfish Pelteobagrus fulvidraco. (February 2016) - Song, Yu-Feng; Luo, Zhi; Zhang, Li-Han; Hogstrand, Christer; Pan, Ya-Xiong
Abstract: The present study was conducted to investigate the effect of Cu exposure on ER stress and Ca 2+ homeostasis, and explore the underlying mechanism of the ER stress and disturbed Ca 2+ homeostasis in the regulation of hepatic lipid metabolism in yellow catfish Pelteobagrus fulvidraco . To this end, three experiments were conducted. In experiment 1, P. fulvidraco were exposed to three waterborne Cu concentrations for 56 days. Waterborne Cu exposure evoked ER stress and SREBP-1c activation and resulted in dysregulation of hepatic lipid metabolism in liver of P. fulvidraco in a time-dependent manner. In experiment 2, specific inhibitors 2-APB (IP3 receptor inhibitor) and dantrolene (RyR receptor inhibitor) were used to explore whether Ca 2+ release from ER was involved in the Cu-induced ER stress change. Dantrolene and 2-APB prevented Cu-induced intracellular Ca 2+ elevation, demonstrating that the release of Ca 2+ from the ER, mediated by both RyR and IP3R, contributed to dysregulation of lipid metabolism. In experiment 3, a chemical chaperone (PBA) was used to demonstrate whether Cu-induced alteration in lipid metabolism was suppressed through the attenuation of ER stress. PBA attenuated the Cu-induced elevation of mRNA expression of SREBP-1c, SCAP, ACC, FAS, GRP78/BiP, GRP94, CRT, eIF2α and XBP-1, and alleviated the Cu-induced downregulation of Insig-1. Based on these observations, these results reveal a link between ER stress and the change of lipid metabolism induced by Cu, which will help to understand the Cu-induced toxicity on cellular and molecular level, and provide some novel insights into the regulation of lipid metabolism in fish. Highlights: ER stress contributes to lipid accumulation in Cu-evoked change of lipid metabolism. The release of Ca 2+ from the ER contributed to dysregulation of lipid metabolism. Cu-induced alteration in lipid metabolism was suppressed through the attenuation of ER stress.